The Medieval Quiet Period. (June 2016) - Bradley, Raymond S; Wanner, Heinz; Diaz, Henry F.
For several centuries in early Medieval times the climate system was relatively unperturbed by natural forcing factors, resulting in a unique period of climate stability. We argue that this represents a reference state for the Common Era, well before anthropogenic forcing became the dominant driver of the climate system.